Impact of Different Energy Sources on Some Performance Parameters of Japanese quail - Sarood Samal Shawkat; Rozhgar Baiz Saeed (University of Thi-Qar Journal of agricultural research, 2025)
This stud proved fulfilling its objectives about the growth performance, feed intake, feed efficiency, production efficiency and profit from quails under five different energy sources of dietary oil: unmixed oil control (T1) oil addition at the rate of 1% of the diet of corn oil (T2), sunflower oil (T3), soybean oil (T4), and tallow (T5) and 440 birds randomly assigned to treatment groups. All 7 diets were modeled to meet isonitrogenous and isocaloric levels set by NRC 1994. Performance was tracked over 6 weeks and data analyzed in a completely randomized design. Though early growth (1–14 days) showed little change, at the end of the trial, soybean oil (T4) improved final body weight (247.483 g), and body weight gain (265.163 g) at the low FCR (1.567) than the control. The Feed intake in this treatment was also lowest compared to the rest (418.370 g), indicating improved energy efficiency. The production index from treatment group T4 was also the greatest, in addition to having favorable economic returns. This supports other studies suggesting that vegetable oil, and particularly soybean oil, increases apparent digestibility of nutrients, enzyme functions, and lipid metabolism in poultry. The soybean oil also contains bioactive molecules like lecithin that aids in fat digestion and cholesterol control. Scientific and economic principles regarding Japanese Quail biomass production systems suggest that substituting with soybean oil instead of solid animal fats or carbohydrate sources adds margin